Adaptación climática y respuesta de doce materiales genéticos de soya (Glycine max L. Merril), sembrado en la época seca, en el Cantón Quevedo. - Pincay Rivera, Carlos Lenin (2008)
The present investigation was carried out it in the Experimental Property The María", of property of the State Technical University of Quevedo, which is located in the Km. 7 ½ of the road to El Empalme, Cantón Quevedo, County of Los Ríos. Their geographical location is 01°06 of south latitude and 79°29 ' of longitude west, to a height of 120 m on the level of the sea. He/she thought about the general objective: To evaluate the answer in grain of twelve genetic materials of soya, introduced of Colombia and fields in the dry time and the specific ones: To determine the genetic material of more adaptation to the study area; To evaluate the productive potential of introduced materials of Colombia, in comparison with local commercial varieties and to Carry out the economic analysis, in function of the yield level and cost of the cultivation. Subject to the following hypothesis: The lines of introduced soya, are superior in yield to the local varieties. The genetic materials that were used in the present investigation were 12 more 2 commercial witness. A design of Complete Blocks was used at random (DBCA), with 14 treatments and 4 repetitions. All the variables in study were subjected to the variance analysis and for the comparison of the stockings of the treatments the test Tukey was used to 95% of probabilities. The most precocious materials to the flowing (40 days) they were SL-2, SL-19, SL-20 y P-34, being their probable cause the precocity of their progenitors and the conditions existent agro climatic in the area of the rehearsal. The plant height was similar statistically in all the varieties, being been possibly to the adaptability from these to the climatic conditions. The materials SL-2 and SL-11, showed bigger resistance to the one it flattens, being inferior in 6,79% and 7,15% with relationship at the INIAP-307 which showed the biggest percentage of it flattens with 7,86%. The characters number branches for plant, weight of 100 grains and percentages of sheaths with 1, 2, 3 and 4 seeds for sheath, they showed certain degree of variability between the commercial varieties and the experimental ones, being observed that the experimental lines Kamerún and SL-21 presented the biggest quantity in branches for plant. The biggest weight of 100 grains, showed it the experimental line SL-5. The experimental line SL-20 and the Kamerún presented the biggest percentage of sheaths with 3 grains. The biggest yields of grains and the biggest economic yield was presented in the experimental line SL-2 with 2073,75 kg ha-1, followed by the Soyica P-34 with 1948,87kg ha-1.